Comparison of Single- Versus Dual-Vector Technique Using Facial Suspension Threads: A Cadaveric Study Using Skin Vector Displacement Analysis. Issue 12 (December 2020) - Liew, Steven; Frank, Konstantin; Kolenda, Jack; Braun, Martin; Cotofana, Sebastian
Abstract : BACKGROUND: Facial suspension threads have been successfully used for facial soft-tissue repositioning. When using facial suspension threads, it is unclear which technique and/or material has the greatest lifting effect for the middle and lower face or which technique/material best reduces the appearance of the jowls. Material and Methods: Three female and 2 male cephalic specimens of Caucasian ethnicity (65.2 ± 8.3 years; 20.72 ± 2.6 kg/m 2 ) were analyzed in an upright secured position. Polydioxanone and polycaprolactone bidirectional barbed facial suspension threads were introduced by an 18 G, 100 mm cannula. The single-vector technique aimed toward the labiomandibular sulcus, and the dual-vector technique aimed toward the labiomandibular sulcus and the mandibular angle. Computation of vertical lifting, horizontal lifting, and volume reduction at the jowls and along the jawline were calculated using 3D imaging. RESULTS: The dual-vector technique effected a greater vertical lifting effect (4.45 ± 2.78 mm vs 2.99 ± 2.23 mm) but a reduced horizontal lifting effect (0.33 ± 1.34 mm vs 0.49 ± 1.32 mm). The dual-vector technique effected less volume reduction at the jowls 0.32 ± 0.24 cc versus 0.41 ± 0.46 cc and less volume reduction along the jawline 0.46 ± 0.48 cc versus 0.87 ± 0.53 cc (dual-vector vs single-vector). CONCLUSION: This study provides evidence resulting from cadaveric observations for the overall nonsuperiority of the dual-vector technique compared with the single-vector technique. Abstract : Supplemental Digital Content is Available in the Text.